Ampere Meter DC Menggunakan ADC 0804 Sebagai Interface Pada Central Processing Unit (CPU) Komputer - Budi Prijo Sembodo (WAKTU, 2011)
World Science and Technology especially at for computer have giving many amenity all area because it’s operation very practical, efficient and easily. In this research of the peripheral of computer used as by media depicting the level of value measurement of direct current from an external electronics network which interfaced to computer pass to port of parallel. Expected with ampere meter of dc use ADC 0804 as interface at central processing unit (CPU) can assist process read of measurement value and can be used also by other consumer in the world of education. The method which is used in this research is descriptive research have the character of developmental, where examination of its data is compared to a standard or criterion which have been specified before when compilation of research design. The result of this research indicate that a software of Delphi version 7.0 from Borland can be used to connect between hardware and software by using components are staying in its environment. The level of comparison between ampere meter of dc use ADC 0804 as interface at central processing unit (CPU) by conventional analog ampere meter equals to 1:1. Ampere meter of dc use ADC 0804 as interface at Central Processing Unit (CPU) have comparison which is equal to conventional analog ampere meter so that ampere meter of dc use ADC 0804 as interface at Central Processing Unit (CPU) have reliable.